Interaction of the lipoprotein lipase asparagine 291→serine mutation with body mass index determines elevated plasma triacylglycerol concentrations: a study in hyperlipidemic subjects, myocardial infarction survivors, and healthy adults. - Fisher, Rachel M.; Mailly, France; Peacock, Rachel E.; Hamsten, Anders; Seed, Mary; Yudkin, John S.; Beisiegel, Ulrike; Feussner, Giso; Miller, George; Humphries, Steve E.; Talmud, Philippa J. (Journal of lipid research, 1996)
A mutation in the lipoprotein lipase (LPL) gene, resulting in the substitution of asparagine by serine at residue 291 (LPL-S291), was found to occur in young survivors of a myocardial infarction from Sweden, combined hyperlipidemic subjects from the United Kingdom, and type III hyperlipidemic subjects from Germany at allelic carrier frequencies no different from those found in companion healthy control subjects (3.63 vs. 3.37; 1.85 vs. 1.60; and 2.00 vs. 1.56%, respectively). In a group of 620 healthy middle-aged men from the United Kingdom with baseline and three subsequent annual lipid measurements, mean plasma triacylglycerol (TG), (but not plasma cholesterol) concentrations in carriers of the mutation were significantly elevated over non-carriers (1.95 vs. 1.61 mmol/l, P = 0.05, and 5.83 vs. 5.65 mmol/l, P = 0.29, respectively). When these healthy control subjects were divided according to tertiles of body mass index (BMI), as expected, non-carriers whose BMI was in the upper two tertiles (BMI > or = 25.0 kg/m2) had higher plasma TG concentrations than those in the lowest tertile (1.90 vs. 1.54 mmol/l), but this difference was much greater in LPL-S291 carriers (2.33 vs. 1.36 mmol/l, P = 0.01, BMI x genotype interaction, P = 0.02). To confirm this effect, a second group of 319 healthy subjects from the United Kingdom was screened for LPL-S291. The allelic frequency of the mutation was found to be 1.88% and the effect on plasma lipid concentrations was very similar to that observed in the first control group (plasma TG, 2.31 vs. 1.27 mmol/l, P < 0.001 for LPL-S291 carriers vs. non-carriers, respectively). As before, those carriers whose BMI was in the top two tertiles for this sample (BMI > or = 23.3 kg/m2) had higher plasma TG concentrations than non-carriers (2.31 vs. 1.42 mmol/l). Thus, the LPL-S291 variant may predispose individuals to elevated plasma TG concentrations under conditions such as increased BMI.